Les fondements de la déontologie judiciaire - Huppé, Luc (Les Cahiers de droit, 2004)
Although the judicial function is of the utmost importance for the society, there is much uncertainty in Canada about the rules governing judicial ethics. Contrary to the judges appointed by the government of Québec, the judges appointed by the federal governement are not bound by a code of judicial ethics. This situation raises the question of the sources of judicial ethics in Canada. The legal foundations of judicial ethics are to be found in the judicial oath taken by each person assuming judicial functions and in the intrinsic requirements of the judicial function.